Mouse renal 4T1 cell engraftment as a model to study the influence of hypoxia in breast cancer progression - Heriton Marcelo Ribeiro Antonio; Larissa Raquel Mouro Mandarano; Alan Augusto Coelho; Marcelo Guimarães Tiezzi; Jurandyr Moreira de Andrade; Daniel Guimarães Tiezzi (Acta Cirúrgica Brasileira, 2013)
PURPOSE: To develop a mouse model to study the influence of hypoxia in breast cancer progression and metastasis. METHODS: The 4T1 cell line was used to engraft the kidneys of female BALB/c mice. Placing an aneurysm clip on the kidney hilum, hypoxia can be directed to tumor site. Histological evaluation was used to analyze the morphological changes induced by ischemia in kidney cortex, and to verify the metastatic potential. RESULTS: 4T1 cells can be engrafted into the renal cortex and the renal ischemia caused by using a clip to clamp the renal hilum induces hypoxia at the tumor site. This procedure maintains the ability of 4T1 cells to metastasize. In fact, our preliminary results showed that tumor hypoxia precipitates the metastatic dissemination of tumor cells. After 14 days of engraftment, lung metastases were observed only in mice that were subjected to tumor hypoxia. CONCLUSION: This model can help us to understand how low oxygen tension mediates hypoxia-induced proteomic and genomic changes in breast cancer.